Internet of Vehicles -- Technologies and Services First International Conference, IOV 2014, Beijing, China, September 1-3, 2014, Proceedings - Hsu, Robert C.-H.; Shangguang, Wang.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2014)
This book constitutes the refereed proceedings of the first International Conference on Internet of Vehicles, IOV 2014, held in Beijing, China, in September 2014. The 41 full papers presented were carefully reviewed and selected from 160 submissions. They focus on the following topics: IOV systems and applications; wireless communications, ad-hoc and sensor networks; security, privacy, IoT and big data intelligence; cloud and services computing.
IOV systems and applications -- Wireless communications -- Ad-hoc and sensor networks -- Security, privacy, IoT and big data intelligence -- Cloud and services computing.
Keywords: 9; Application software; Information storage and retrieval systems; Database management; Algorithms; Electronic data processing -- Management; Computer Communication Networks; Computer and Information Systems Applications; Information Storage and Retrieval; Database Management; Algorithms; IT Operations